RAJAH DALAM TRADISI MASYARAKAT ACEH - Rizka utami; Nisa Auliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Antasari Banjarmasin, 2024)
Abstract: Some people in Aceh believe that there are individuals who possess the ability to call upon guardian spirits or khadam that protect them. This is known as